ANTI-HCV ANTIBODIES DETECTION-A COMPARISON BETWEEN METHODOLOGY: ELISA VS DIPSTICK ASSAY - Sheikh, Shahid Mahmood; Tayyab, Muhammad; Jaffary, Ghazala; Tasneem, Tahira; Sattar, Abdul; Ali, Iftikhar (Journal of Ayub Medical College Abbottabad, 1999)
Hepatitis C accounts for 70-95% cases of post-transfusion hepatitis in different parts of the world. The high prevalence of antibodies to hepatitis C virus (HCV) among frequently blood transfused patients (e.g. thalassaemic), those who receive blood products (e.g. haemophiliacs), and among intravenous drug abusers confirmed the parenteral route as the major route of HCV infection. To promote screening of blood donors for HCV antibodies, a Dipstick HCV assay was compared with third generation enzyme immunoassay. Fifty diagnosed cases of hepatitis C and twenty healthy control subjects were analyzed by both methods and hundred per cent same results were found.